Unemployment Period Approach with Infinite Servers Queue Systems - Ferreira, M. A. M. (EasyChair Preprint Nº 7966, 2025)
This article is based on the work of (Ferreira, Filipe and Coelho, 2016) presented at International Conference Quantitative Methods in Economics (Multiple Criteria Decision Making XVIII). There using results on the infinite servers queue systems with Poisson arrivals - M|G|∞ queues - busy period, it is presented an application of those queue systems in the unemployment periods time length parameters and distribution function study. These queue systems are adequate to the study of many population processes, and this quality is brought in here. The results presented are mainly on unemployment periods length and their number in a certain time interval. Also, some questions regarding the practical applications of the outlined formulas are briefly discussed.